Trump, Kierkegaard, and a nation divided. Issue 1 (27th November 2019) - Thompson, Curtis L.
Abstract: This article depicts the United States as a nation divided, as it suffers from two major deficiencies: in societal income equality and in individual formation of selves. It offers reflections on how Søren Kierkegaard's writings and those of Kierkegaard‐world are a resource for critiquing Donald Trump and addressing the disruption and divisiveness he and Trump‐world are bringing to America's national life. Contours of a theological ethic focusing on the formation of ethical selves are delineated and examples of practicing resurrection are given.